History Development Instruments Measuring The Qibla In Indonesia - Zahara Suciani Putri; Muhib Rosyidi (al-Afkar, Journal For Islamic Studies, 2024)
The execution of the prayer, a fundamental duty for Muslims, encompasses a range of prerequisites, pillars, recommended practices, manners, and restrictions that should be adhered to during the act of worship. A crucial condition for a prayer to be deemed valid involves aligning oneself with the Qibla (the Ka’bah in Masjidil Haram) in the city of Mecca, a consensus reached by scholars. Consequently, there exists a necessity for tools that simplify the determination of the Qibla's direction. Over time, instruments for gauging the Qibla's orientation have evolved significantly, progressing from basic reference objects to user-friendly systems, ultimately leading to a reduction in the time required for measurement. This article will delve into the history of Qibla direction measurements in Indonesia using various methods, ranging from classical to modern approaches. The research employs a qualitative method with a literature review technique, aiming to reveal the historical development of Qibla direction measurements in Indonesia. The obligation to face the Qibla, with technological advancements, necessitates that regulations regarding the Qibla direction follow better guidelines to enhance the strength of worship implementation. Despite science providing information, religious authorities remain the ones to establish its laws.